Pragmatic algorithm for visual assessment of 4-Repeat tauopathies in [18F]PI-2620 PET Scans - Theresa Bauer; Matthias Brendel; Mirlind Zaganjori; Alexander M. Bernhardt; Alexander Jäck; Sophia Stöcklein; Maximilian Scheifele; Johannes Levin; Thilo van Eimeren; Alexander Drzezga; Osama Sabri; Henryk Barthel; et al. (NeuroImage)
Aim: Standardized evaluation of [18F]PI-2620 tau-PET scans in 4R-tauopathies represents an unmet need in clinical practice. This study aims to investigate the effectiveness of visual evaluation of [18F]PI-2620 images for diagnosing 4R-tauopathies and to develop a straight-forward reading algorithm to improve objectivity and data reproducibility. Methods: A total of 83 individuals with [18F]PI-2620 PET scans were included. Participants were classified as probable 4R-tauopathies (n = 29), Alzheimer's disease (AD) (n = 20), α-synucleinopathies (n = 15), and healthy controls (n = 19) based on clinical criteria. Visual assessment of tau-PET scans (choice: 4R-tauopathy, AD-tauopathy, no-tauopathy) was conducted using either 20–40-minute or 40–60-minute intervals, with raw (common) and cerebellar grey matter scaled standardized reading settings (intensity-scaled). Two readers evaluated scans independently and blinded, with a third reader providing consensus in case of discrepant primary evaluation. A regional analysis was performed using the cortex, basal ganglia, midbrain, and dentate nucleus. Sensitivity, specificity, and interrater agreement were calculated for all settings and compared against the visual reads of parametric images (0–60-minutes, distribution volume ratios, DVR). Results: Patients with 4R-tauopathies in contrast to non-4R-tauopathies were detected at higher sensitivity in the 20–40-minute frame (common: 79%, scaled: 76%) compared to the 40–60-minute frame (common: 55%, scaled: 62%), albeit with reduced specificity in the common setting (20–40-min: 78%, 40–60-min: 95%), which was ameliorated in the intensity-scaled setting (20–40-min: 91%, 40–60-min: 96%). Combined assessment of multiple brain regions did not significantly improve diagnostic sensitivity, compared to assessing the basal ganglia alone (76% each). Evaluation of intensity-scaled parametric images resulted in higher sensitivity compared to intensity-scaled static scans (86% vs. 76%) at similar specificity (89% vs. 91%). Conclusion: Visual reading of [18F]PI-2620 tau-PET scans demonstrated reliable detection of 4R-tauopathies, particularly when standardized processing methods and early imaging windows were employed. Parametric images should be preferred for visual assessment of 4R-tauopathies.